Interactions between Mycoplasma pneumoniae and guinea pig complement. - Bredt, W (1975)
The "toxic" effect of guinea pig serum (GPS) on Mycoplasma pneumoniae cells was tested under various conditions, using rounding and killing of the cells as test systems. Both activities could be inhibited by heat inactivation (56 C, 30 min). Killing required both Ca2+ and Mg2+, rounding only Mg2+. Both activities were temperature dependent and no rounding or killing occurred at 4C. Incomplete complement sequences with natural of artificial defects in C1, C4, or C6 resulted in lost or reduced killing. The rounding activity was only slightly affected. Anti-C3 antiserum blocked both phenomena; incubation of GPS with 10 mg of inulin per ml reduced the rounding activity, and the same treatment of GPS deficient in C4 inhibited rounding totally. Properdin factor D was shown to be necessary for rounding by GPS, with defects in either C1 or C4. By immune adherence bound C3b could be demonstrated on M. pneumoniae cells after GPS treatment, no antibodies against M. pneumoniae could be found in GPS by immune fluorescence. The results give evidence for complement being the toxic factor in GPS. Efficient killing requires the intact complement sequence. Furthermore, M. pneumoniae cells are able to activate the alternate pathway of complement. Activation of this pathway results in rounding of the cells, which are partly able to recover after this reaction. Biological consequences for the mycoplasmas are death or damage and possibly opsonization, even in the absence of specific antibodies. The host, too, is possibly affected by products of the reaction. The interaction of M. pneumoniae and complement could be involved in the early stages of the development of M. pneumoniae disease.